Effect of increased lactate dehydrogenase A activity and aerobic glycolysis on the proinflammatory profile of autoimmune CD8+ T cells in rheumatoid arthritis - Souto-Carneiro, Maria Margarida; Klika, Karel D.; Abreu, Mónica T.; Meyer, André P.; Saffrich, Rainer; Sandhoff, Roger; Jennemann, Richard; Kraus, Franziska V.; Tykocinski, Lars-Oliver; Eckstein, Volker; Carvalho, Lina; Kriegsmann, Mark; et al. (Arthritis & rheumatology, 2020)
Objective - CD8+ T cells contribute to rheumatoid arthritis (RA) by releasing proinflammatory and cytolytic mediators, even in a challenging hypoxic and nutrient-poor microenvironment such as the synovial membrane.